2023
DOI: 10.3346/jkms.2023.38.e189
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Prescription in Patients With Coronavirus Disease 2019: Analysis of National Health Insurance System Data in the Republic of Korea

Abstract: Background Although coronavirus disease 2019 (COVID-19) is a viral infection, antibiotics are often prescribed due to concerns about accompanying bacterial infection. Therefore, we aimed to analyze the number of patients with COVID-19 who received antibiotic prescriptions, as well as factors that influenced antibiotics prescription, using the National Health Insurance System database. Methods We retrospectively reviewed claims data for adults aged ≥ 19 years hospitalize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…A study conducted in Korea on the use of antibiotics in COVID-19 patients revealed that advanced age and comorbidities were associated with frequent antibiotic prescription. 24 In our study, both the omicron and influenza groups, which are characterized by older age and a higher prevalence of comorbidities compared to the pre-omicron group, may have experienced increased antibiotic usage. Additionally, baseline characteristics and antibiotic use patterns were similar in the omicron and influenza groups.…”
Section: Dicussionmentioning
confidence: 66%
“…A study conducted in Korea on the use of antibiotics in COVID-19 patients revealed that advanced age and comorbidities were associated with frequent antibiotic prescription. 24 In our study, both the omicron and influenza groups, which are characterized by older age and a higher prevalence of comorbidities compared to the pre-omicron group, may have experienced increased antibiotic usage. Additionally, baseline characteristics and antibiotic use patterns were similar in the omicron and influenza groups.…”
Section: Dicussionmentioning
confidence: 66%
“…Regarding irrational antibiotic use, the COVID-19 pandemic was not an exception. Several studies have evaluated antibiotic use during the pandemic [29,30]. Vâţă et al conducted a retrospective study to assess antibiotic use practices in critically ill patients.…”
Section: Discussionmentioning
confidence: 99%